2012
DOI: 10.14411/eje.2012.006
|View full text |Cite
|
Sign up to set email alerts
|

The role of mosaicity of the post-agriculture area of the Kampinos National Park in determining the diversity of species of spider wasps (Hymenoptera: Pompilidae)

Abstract: Abstract. From 2000 to 2006 a total of 52 CPUE samples of spider wasps (Hymenoptera: Pompilidae) were collected in the mosaic landscape of the Kampinos National Park (Poland), which is a UNESCO Biosphere Reserve. The hypothesis tested was that both pompilid species richness and abundance is positively associated with spatial heterogeneity. The patterns in spider wasp assemblages were identified using a Kohonen artificial neural network (i.e., self-organizing map). The highest numbers and greatest species richn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 46 publications
2
24
0
Order By: Relevance
“…; Table ). The high species diversity of aculeates has been already reported for different types of anthropogenic habitats including wooden and clay buildings (Banaszak, ; Rosa, , ; Bennett et al ., ; Szczepko et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…; Table ). The high species diversity of aculeates has been already reported for different types of anthropogenic habitats including wooden and clay buildings (Banaszak, ; Rosa, , ; Bennett et al ., ; Szczepko et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The presence of a more diverse neighbourhood could increase the availability of pollen and nectar, hosts and refuges from disturbances including over‐wintering sites (Dunning et al ., ; Tscharntke et al ., , , ; Weibull et al ., ; Steffan‐Dewenter, ; Steffan‐Dewenter et al ., ). A number of authors have reported similar effects of the surrounding matrix with moths (Ricketts et al ., ), butterflies (Ricketts, ; Tscharntke et al ., ), plant‐hoppers (Haynes & Cronin, ), flea beetles (Jonsen et al ., ), trap‐nesting bees and wasps (Steffan‐Dewenter, ), and spider wasps (Szczepko et al ., ). A good example is the species richness of sphecid wasps in moist meadows in Hungary, which also depends on the heterogeneity of the surrounding landscape rather than the conditions in the meadows sampled: a higher number of species was recorded in meadows surrounded by dry sandy hills covered with flowering plants than in a meadow with neighbouring habitats having heavier soils (Benedek, ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In many cases this contributed to the incompatibility of pine tree stands with the habitat. It distinguishes species significantly associated with a phytocoenosis at a specific time, which can then be used to observe succession‐related transformations of a forest community; it has been proven that the IndVal is especially effective in this respect when applied to organisms lacking the ability to actively move (Penczak ), It provides information on the habitat preferences of species, which may be useful for their protection in nature reserves (Szczepko et al. ), The comparison of ecological indicators for vascular plants between sub‐clusters of PRs distinguished by SOM helps to indicate the crucial abiotic factors shaping the plant communities.…”
Section: Discussionmentioning
confidence: 99%